A free boundary problem for a class of nonlinear nonautonomous size-structured population model. Issue 16 (10th December 2018) - Lv, Wenbin; Wu, Shaohua
ABSTRACT: In this paper, we study a free boundary problem for a class of nonlinear nonautonomous size-structured population model. Using the comparison principle and upper–lower solution methods, we establish the existence of the solution for such kind of a model.